The strengths and opportunities for improvement of the Baldrige Performance Excellence Program. Issue 3 (3rd July 2021) - Ghafoor, Saad; Mann, Robin Stephen; Grigg, Nigel
Abstract: This research investigates the strengths and opportunities for improvement of the National Institute of Standards and Technology's (NIST's) Baldrige Performance Excellence Program (BPEP) in terms of designing the Malcolm Baldrige Excellence Framework (MBEF) and its deployment (promoting the MBEF, facilitating its use, and awarding Business Excellence (BE)) within the United States. Data were collected directly from NIST and compared to the data from 28 other BE Custodians (BECs) from 26 countries to identify the BE promotion, facilitation, and award related activities that the other BECs could learn from the BPEP and the best practices that the BPEP could learn from the other BECs. It was found that BPEP's key strengths are a) the design of the MBEF, with 34.5% of BECs adopting it, second only to the EFQM with 44.8% adopters b) the awards process is robust with NIST rating its processes in this area more highly than in other areas. The BPEP's key opportunities for improvement were in increasing the awareness of BE and facilitating organizations to use a BE approach. Recommendations are provided on how the BPEP can be improved, with examples of practices used by other BECs.